Kajian Penggunaan Surfaktan dan Sel Bebas Pada Pembuatan Bioetanol Dari Nira Nipah Kental - M. Bayu Purwanto; Fajar Restuhadi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The aim of the research was to obtain the best combination treatment between early sugar concentration and Tween80 concentration as surfactant and nutrition for Saccaromyces cerevisiae to produce ethanol on very high gravity fermentation from Nypa sap. The exploration research used two factor treatments with two replications. The treatments consist of early sugar concentration N1 (20%), N2 (25%), N3 (30%) and Tween80 concentration T0 (0%), T1 (0,2%), T2 (0,4%), T3 (0,6%). Observation was conducted every 24 hours i.e sugar concentration, ethanol concentration, amount of cell, and pH. Data obtained were analyzed by descriptive method. The best combination treatment was T3N2 (Tween80 0,6% and N 25%) which produced ethanol 17,25%.   Keywords: Nypa sap, Tween80, Bioethanol, Very High Gravity Fermentation